Polariscope for injection molded component testing - Sng, Eunice Kiat Yee (2017)
This A113 project was to modify existing d'Polariscope to create a new equipment that simplify process, shorten test run time and achieve a more accurate results. The designing was done using Modular Function Deployment. With the new technique integrated into the system, multiply tests were conducted to identify procedure that allows fast test runs and accurate results. The tests conducted will be focusing on the results collected based on difference settings and the thickness of sample pieces. Furthermore, there would be marketing research done on the new equipment.